Sombras de lo real - Monegal, Antonio (Rassegna Iberistica, 2016)
The current stage of the observations on the relationship between the Arts allows us to move past the model of comparison between literary and visual works of art and address the inherent complexity of mixed models and cultural products that embody this difference. Such considerations send us back to the origins of the interartistic debate, to rethinking the arts’ mimetic ability in a context where the acknowledgement of cultural field is an invitation to investigate the relational dynamics. The case study is a brief video by Víctor Erice, filmed while preparing for the shooting of the documentary El sol del membrillo, on the painting of Antonio López.